2020
DOI: 10.1007/s10120-020-01076-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Helicobacter pylori eradication after subtotal gastrectomy on the survival rate of patients with gastric cancer: follow-up for up to 15 years

Abstract: Objective Helicobacter pylori (HP) is known to play an important role in the development of gastric cancer (GC). The aim of this study was to analyze the effect of HP eradication on the survival rate and cancer recurrence in patients who underwent subtotal gastrectomy for GC. Design Totally 1,031 patients diagnosed with gastric adenocarcinoma who received surgical treatment at the Seoul National University Bundang Hospital from 2003 to 2017 and positive for HP infection were analyzed. The overall and GC-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The present study observed the death and recurrence events in the first 18 months after surgery of GC patients. According to the results of several large clinical studies, [36][37][38] the mortality in the first 18 months after section of GC patients accounted for about half of the long-term (5-10 years) mortality. Therefore, the death events in the first 18 months after surgery can objectively reflect the short-term survival rate, and can to some extent reflect the long-term survival status of GC patients.…”
Section: Open Accessmentioning
confidence: 99%
“…The present study observed the death and recurrence events in the first 18 months after surgery of GC patients. According to the results of several large clinical studies, [36][37][38] the mortality in the first 18 months after section of GC patients accounted for about half of the long-term (5-10 years) mortality. Therefore, the death events in the first 18 months after surgery can objectively reflect the short-term survival rate, and can to some extent reflect the long-term survival status of GC patients.…”
Section: Open Accessmentioning
confidence: 99%
“…However, one prospective study of eradication of HP after gastrectomy reported that atrophic gastritis and intestinal metaplasia were associated with spontaneous disappearance of HP [10]. Some retrospective studies have reported that HP eradication after gastrectomy in uences long-term prognosis, but no consensus has been reached [4][5][6][7]11,12]. In addition, previous reports did not consider the possibility of spontaneous disappearance of HP after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some reports of HP eradication after gastrectomy, including EGC and advanced GC (AGC) [6,7], there are no reports on the natural history of HP after gastrectomy. The aim of this trial was to evaluate the status of postoperative HP infection in our hospital in patients with preoperative HP infection.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Wang et al, the expression level of miR-187-5p was significantly lower in diffuse-type gastric cancer tissue than in normal gastric tissue [ 29 ], suggesting that the damaged gastric tissue surrounding the cancer site could release miR-187-5p. Notably, exosomes derived from normal gastric epithelial cells function to inhibit the progression of gastric cancer [ 30 , 31 ]. miR-187-5p has a tumor-suppressive effect in non-small-cell lung cancer [ 32 ]; therefore, the active release of miR-187-5p from the tumor microenvironment might play a role in suppressing tumor growth.…”
Section: Discussionmentioning
confidence: 99%